Repurposing Approved Immunomodulatory Drugs for Target Proteins in the Pancreas of European eel: A Molecular Docking Approach - Varalakshmi T.S. (International Journal of Molecular Biotechnological Research, 2025)
Leishmaniasis is a disease caused by tiny parasites called Leishmania, which spread to humans through the bite of an infected female sand fly. The disease manifests in three different forms, and the protein calcitonin promotes the disease’s spread. By reducing blood calcium levels, inhibiting osteoclast activity, increasing calcium excretion, and possibly playing a role in neurotransmitter modulation, calcitonin, a hormone released by vertebrates, promotes the progression of pathogenesis and lessens the load for parasites. The goal of the current investigation is to identify immunomodulatory medications that target the calcitonin protein. Drug banks and PubChem provided information for the molecular docking process, PyRx handled the docking process, and Biovia handled visualization, protein-ligand defining and the acquisition of 3D and 2D structures. To analyze protein flexibility, identify structural errors, and validate protein structure predictions, a Ramachandran plot was constructed, and other tools were used for pharmacological studies. Finally, Eplerenone and Saxagliptin are the two candidates selected as potential drugs to treat the leishmaniasis. Both Eplerenone and Saxagliptin help in reducing the spreading of leishmaniasis by binding to the calcitonin protein present in humans, which alters the immune responses in the body.
Keywords: Biovia discovery studio; CD4 T-cell; CD8 T-cell; PyRx; Ramachandran plot; drug bank database; food and drug administration; immunomodulatory drugs